2010
DOI: 10.1002/jcb.22457
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of human FE65, a ligand of Alzheimer's disease amyloid precursor protein, by Sp1

Abstract: FE65 is a neuronal-enriched adaptor protein that binds to the Alzheimer's disease amyloid precursor protein (APP). FE65 forms a transcriptionally active complex with the APP intracellular domain (AICD). The precise gene targets for this complex are unclear but several Alzheimer's disease-linked genes have been proposed. Additionally, evidence suggests that FE65 influences APP metabolism. The mechanism by which FE65 expression is regulated is as yet unknown. To gain insight into the regulatory mechanism, we clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…We found that a preponderance of the most highly-represented genes in our enriched pathways were constituents of a transcriptional regulation network driven by the SP1 transcription factor (Figure 4). The SP1 transcription factor has known binding regions in the promoters of genes related to beta-amyloid precursor protein (Yu et al 2010; Rossner et al 2006), tau protein (Santpere et al 2006), and APOE . In particular, SP1 has been proposed as a regulator of APOE promoter activity in relation to two promoter polymorphisms with significant association to AD (Maloney et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We found that a preponderance of the most highly-represented genes in our enriched pathways were constituents of a transcriptional regulation network driven by the SP1 transcription factor (Figure 4). The SP1 transcription factor has known binding regions in the promoters of genes related to beta-amyloid precursor protein (Yu et al 2010; Rossner et al 2006), tau protein (Santpere et al 2006), and APOE . In particular, SP1 has been proposed as a regulator of APOE promoter activity in relation to two promoter polymorphisms with significant association to AD (Maloney et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This clone was reactive with 52% of WT sera collected by SIOP but only with 12% of sera from non‐WT controls. The protein that is a member of the Fe65 protein family interacts with the amyloid precursor protein and downregulates thymidylate synthase expression in Alzheimer's disease 41…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of 14-3-3γ by Gal4-AICD fusion protein enhances Fe65-dependent gene transactivation by two-fold in mouse neuroblastoma-2a cells (53). Recently, Sp1 was reported to play a crucial role in transcriptional regulation of human Fe65 (54). In contrast, X11α has an inhibitory effect on AICD-mediated gene transactivation by trapping AICD in the cytoplasm (42).…”
Section: Role Of Aicd In Transcriptionmentioning
confidence: 99%